2004
DOI: 10.1111/j.0001-6349.2004.00481.x
|View full text |Cite
|
Sign up to set email alerts
|

Review of nonsurgical and surgical treatment and the role of insulin‐sensitizing agents in the management of infertile women with polycystic ovary syndrome

Abstract: Diet and exercise followed by CC should be used for nonsurgical ovulation induction. For CC-resistant PCOS women, metformin may be included in a stepwise approach before a surgical approach. LOD with electrocautery is superior to laser drilling and gonadotropin therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 81 publications
(93 reference statements)
2
25
0
2
Order By: Relevance
“…LOD with elecrocautery was found to be superior in treating anovulation compared to laser drilling or use of gonadotropins in clomiphene-resistant PCOS patients. The major side effects of LOD are the fact that it is a theater procedure and requires anesthesia; it may reduce ovarian reserve and has been associated with peri-ovarian adhesions [29,30]. When ranked according to efficacy of ovulation induction, the systemic review found out that the clomiphene citrate in combination with metformin was the most efficacious followed by follicle-stimulating hormone, letrozole, metformin, clomiphene, tamoxifen, laparoscopic ovarian drilling, and placebo or no treatment in that order.…”
Section: Surgery and Ovulation Induction 41 Use Of Ovarian Drillingmentioning
confidence: 99%
“…LOD with elecrocautery was found to be superior in treating anovulation compared to laser drilling or use of gonadotropins in clomiphene-resistant PCOS patients. The major side effects of LOD are the fact that it is a theater procedure and requires anesthesia; it may reduce ovarian reserve and has been associated with peri-ovarian adhesions [29,30]. When ranked according to efficacy of ovulation induction, the systemic review found out that the clomiphene citrate in combination with metformin was the most efficacious followed by follicle-stimulating hormone, letrozole, metformin, clomiphene, tamoxifen, laparoscopic ovarian drilling, and placebo or no treatment in that order.…”
Section: Surgery and Ovulation Induction 41 Use Of Ovarian Drillingmentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS) is a prevalent and heterogeneous condition affecting 6–10% of reproductive‐aged women and 35–40% of infertile women 1,2 . It is the most common cause of chronic anovulation 1,3 , 4 . Patients may also present with menstrual irregularities (usually oligo‐ or amenorrhea), hirsutism, acne or a combination of these.…”
Section: Introductionmentioning
confidence: 99%
“…Women with PCOS have an increased prevalence of impaired glucose tolerance (35–40%) and a prevalence of type 2 diabetes mellitus (7.5–10%) 7,8 . Furthermore, long‐term risks of metabolic consequences in women with PCOS who are characterized by insulin resistance are also increased, including dyslipidemia, hypertension, coronary artery disease and endometrial carcinoma 1,7–9 …”
Section: Introductionmentioning
confidence: 99%
“…In obese women with PCOS, physical activity and low-calorie diet intake lead to an improvement in ovarian function and reduction of the risk of type 2 diabetes mellitus [18]. Exercise and weight control are highly recommended because of their direct effect not only on the metabolic framework but also on ovarian function and restoration of fertility [19].…”
Section: Obesitymentioning
confidence: 99%